PERSEPSI DOSEN TERHADAP PENGARUH KURIKULUM MERDEKA TERHADAP PEMBELAJARAN BAHASA ARAB BERBASIS KOMPETENSI - Muhammad Fahrurrozi; Suparmanto Suparmanto; Yaumul Ihsan; Lalu Ridho Alif Triyatma (Program Studi Pendidikan Bahasa Arab Fakultas Tarbiyah IAI Al-Qur'an Al-Ittifaqiah Indralaya, 2025)
The independent curriculum is implemented to deal with the Indonesian education crisis. The application of the curriculum in the field of education is an important basis for an effective and quality learning process. This research aims to determine lecturers' perceptions of the influence of the independent curriculum on competency-based Arabic language learning. The method used is qualitative research. The research results show that the independent curriculum has a positive impact on Arabic language learning.